Respon pertumbuhan dan produksi padi gogo (Oryza sativa L.) terhadap cekaman kekeringan dan pemupukan silika - Nurul Fadhilah; Karno Karno; Budi Adi Kristanto (Journal of Agro Complex, 2021)
ABSTRACT The goal of this research was to study the growth and production of upland rice responing to drought stress and silica fertilization. The research was conducted at greenhouse SPMA H Moenadi, Ungaran, Semarang Regency and Physiology and Plant Breeding laboratory, Diponegoro University, from February to June 2018. The research used factorial design based on completely randomized design. The first factor was silica fertilizers (Control, zeolite and husk ash) and the second factor was drought stress (watering interval 3, 6, 9 and 12 days). The result showed thar silica fertilizer treatment significantly affected the plant growth rate ages 14-30 days after planting, relative growth rate of plant ages 14-30 days after planting, plant height of the 8th week, leaf chlorophyll index of vegetative phase, number of seeds and seed weight, while at drought stress had significant effects on the plant growth rate ages 14-30 days after planting, relative growth rate of plant ages 14-30 days after planting, plant height of week 8 and 15, number of leaves 8 and 15 weeks, generative phase chlorophyll index, number oftillers and productive tillers, number of seeds and seed weight. There was an interaction between silica fertilization and drought stress on the plant growth rate ages 14-30 days after planting, relative growth rate of plant ages 14-30 days after planting and the number of seeds. Keyword : Drought stress, upland rice, silica fertilization ABSTRAK Penelitian ini bertujuan untuk mengkaji pengaruh silika dan cekaman kekeringan terhadap pertumbuhan dan produksi padi gogo. Penelitian dilaksanakan di greenhouse SPMA H. Moenadi, Ungaran, Kab. Semarang dan laboratorium Fisiologi dan Pemuliaan Tanaman, Fakultas Peternakan dan Pertanian, Universitas Diponegoro dari bulan Februari sampai Juni 2018. Rancangan dasar yang digunakan dalam penelitian ini adalah Rancangan Acak Lengkap Faktorial. Faktor pertama yaitu pupuk silika (kontrol, zeolit dan abu sekam) dan cekaman kekeringan (Interval penyiraman 3, 6, 9 dan 12 hari). Hasil penelitian menunjukkan bahwa perlakuan pupuk silika berpengaruh nyata terhadap parameter laju pertumbuhan tanaman umur 14-30 HST, laju pertumbuhan relatif tanaman umur 14-30 HST, tinggi tanaman Minggu ke 8, indeks klorofil daun fase vegetatif, jumlah biji dan bobot biji, sedangkan pada parameter cekaman kekeringan memberikan pengaruh nyata terhadap parameter laju pertumbuhan tanaman umur 14-30 HST, laju pertumbuhan relatif tanaman umur 14-30 HST, tinggi tanaman Minggu ke 8 dan 15, jumlah daun Minggu ke 8 dan 15, indeks klorofil daun fase generatif, jumlah anakan dan anakan produktif, jumlah biji dan bobot biji. terdapat interaksi antara pemupukan silika dan cekaman kekeringan terhadap parameter laju pertumbuhan tanaman umur 14-30 HST, laju pertumbuhan relatif tanaman umur 14-30 HST dan jumlah biji. Kata kunci : Cekaman kekeringan, padi gogo, pemupukan silika